On Perry O. Simons’ 1899 collecting locality “Porvenir” in Ecuador - Cisneros-Heredia, Diego F.; Sherwood, Danniella (Zootaxa, 2024)
The locality of Porvenir, sensu the collecting locality of Perry O. Simons (1869–1901), is geolocated, and approximate coordinates are provided, along with a map showing a number of other important nearby sites also visited by Simons and referenced in the historical zoological literature. Discussion on the incongruent coordinates for this locality mentioned in a number of previous works is provided.